Breeding of Common Bukovinian and Moldavian (BM) Maize Hybrids - А. М. Черномиз; І. С. Микуляк; В. П. Мирза; Н. Г. Ванькович (Plant Varieties Studying and Protection)
Tere are discussed results of joint Bukovino-moldavian corn breeding programmer, as a result which are created two registered hybrids, one perspective, and new material for the further work.